Perspektif Etika Bisnis Islam atas Praktek Jual Beli Baju (study kasus pada pedagang di wisata religi sunan drajat paciran lamongan) - Shofiyah; Kholiq, Abd.; Qomariyah, St. Nur (Al-Musthofa: Journal of Sharia Economics, 2023)
: Buying and selling activities are one of the needs of the community as a means to meet the needs of daily life. Religious tourism is one type of tourism that is closely related to special activites or places related to religious aspects of relifion. In addition, on the tour there are also merchants who sell various kinds ofsouvenirs. Along with the times, which are marked by very rapid economicdevelopment, it creates competition. With this competition, business people use many ways to gain profits, even to the point of ignoring ethics in business. As there are still many who used deviations in sales many who use deviations in salescontained in the tour. The purpose of this study was to find out: (1) Buying and selling practies carried out by traders in religious tourism Sunan Drajat Paciran Lamongan, (2) Islamic business ethics perspective on the practice of buying and selling clothes to traders in religious tourism Sunan Drajat Paciran Lamongan. This research uses descriptive qualitative method with case study type. To collect data is done by interview, observation, and documentation. To prove the validaty of the data using triangulation. Sources and data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the study show that: (1) The practive of buying and selling clothes carried out by traders in Sunan Drajat religious tourism is carried out directly, namely by offering to visitors passing by, (2) Traders in general have carried out in accordance with the principles of Islamic business ethics, including the principles of monotheism, honesty, free will, looseness and generosity, applying transparent prices. Keyword: Business ethics, Islamic, Selling.